Crystal structures and thermal properties of two transition-metal compounds {[Ni(DNI)2(H2O)3][Ni(DNI)2 (H 2O)4]}•6H2O and Pb(DNI)2(H 2O)4 (DNI = 2,4-Dinitroimidazolate) - Zhang, Guo-Fang; Cai, Mei Yu; Jing, Ping; He, Chong; Li, Ping; Zhao, Feng Qi; Li, Ji Zhen; Fan, Xue Zhong; Ng, Seik Weng (Springer Verlag, 2010)
Two transition-metal compounds derived from 2,4-dinitroimidazole, {[Ni(DNI)2(H2O)3][Ni(DNI)2(H 2O)4]}•6H2O, 1, and Pb(DNI) 2(H2O)4, 2, were characterized by elemental analysis, FT-IR, TG-DSC and X-ray single-crystal diffraction analysis. Crystal data for 1: monoclinic, space group C2/c, a = 26.826(3), b = 7.7199(10), c = 18.579(2) Å, β = 111.241(2)° and Z = 4; 2: monoclinic, space group C2/c, a = 6.5347(6), b = 17.1727(17), c = 14.1011(14) Å, β = 97.7248(10) and Z = 4. Compound 1 contains two isolated nickel centers in its structure, one being six-coordinate and another five-coordinate. The structure of 2 contains a lead (II) center surrounded by two chelating DNI ligands and four water molecules in distorted square-antiprism geometry. The abundant hydrogen bonds in two compounds link the molecules into three-dimensional network and stabilize the molecules. The TG-DSC analysis reveals that the first step is the loss of water molecules and the final residue is the corresponding metal oxides and carbon.